O bonapartismo uruguaio nos editoriais do Semanário Búsqueda (1972-1985) - Nunes, Antônio Bezerra (2007)
Our objective was to redeem, by through editorials of Semanario Búsqueda, the construction of liberal hegemony during the military dictatorship in Uruguay, from 1973 until 1985. We search to show your ideas, since 1973, postulating a project of social hegemony, a vision of the world establishmented in the criticize intellectual and moral, objected the defense of reform economic orientated the formation of news socials relationships. Hence, of reading that Búsqueda did in relation the several events. Occurred during the military dictatorship, as, for example, the closure of the congress, the CNT strike under coup storm, the cassations of politicians, the anticommunism, the dialogues between policians parties and militaries point the basis for the redemocratization. We conclude that his ideology had bee in accordance with the decisions of Uruguayan Bobapartismo, claracterized fundamentally for super explorartion of the working class